2021
DOI: 10.1186/s13018-021-02592-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between thoracic kyphosis and age, and normative values across age groups: a systematic review of healthy adults

Abstract: Background Thoracic kyphosis is reported to increase with ageing. However, this relationship has not been systematically investigated. Peoples’ kyphosis often exceeds 40°, but 40° is the widely accepted cut-off and threshold for normality. Consequently, patients may be misclassified. Accurate restoration of kyphosis is important to avoid complications following spinal surgery. Therefore, specific reference values are needed. The objective of the review is to explore the relationship between tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 72 publications
2
13
1
Order By: Relevance
“…For ethical reasons, no such comparative studies based on healthy participants are available. The results presented here, however, reveal a strong functional agreement with the results derived from clinically established measurement approaches, such as X-ray or MRI/CT scans, and VRS measurements [ 33 , 34 , 39 ]. This underlines the potential of VRS to serve as a non-invasive, quick and objective alternative for spinal posture analysis in clinical practice, especially when the therapeutic focus lies in function-orientated clinical outcomes and when pre-post measurements are required.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For ethical reasons, no such comparative studies based on healthy participants are available. The results presented here, however, reveal a strong functional agreement with the results derived from clinically established measurement approaches, such as X-ray or MRI/CT scans, and VRS measurements [ 33 , 34 , 39 ]. This underlines the potential of VRS to serve as a non-invasive, quick and objective alternative for spinal posture analysis in clinical practice, especially when the therapeutic focus lies in function-orientated clinical outcomes and when pre-post measurements are required.…”
Section: Discussionsupporting
confidence: 83%
“…The current study found a trend towards significant differences between young and old ( p < 0.001) and between middle and old ( p < 0.02) participants, indicating an increase in the VRS-measured parameter with increasing age. Comparable results were published in a recent systematic review based on radiography-based Cobb angle calculations [ 33 ]. The authors described an increase in thoracic kyphosis with aging but did not find that sex affected the spine parameters.…”
Section: Discussionsupporting
confidence: 58%
“…Zapallá et al 56 concluded in their systematic review that kyphosis increases with age and varies significantly below 40 years and above 60 years, but not by gender 56 . Single studies could also confirm the correlation between the increase of thoracic kyphosis with age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly described thoracic compensation based on the angle of kyphosis but a mere measurement of kyphotic magnitude might be underpowered for the evaluation of thoracic compensation and the development of PJK. First, there is no consensus on the normal value of TK due to the effect of age and ethnicity 21–23 . The individual heterogeneity of normal TK ranging from 20° to 60° makes it difficult to identify hypokyphosis or hyperkyphosis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…First, there is no consensus on the normal value of TK due to the effect of age and ethnicity. [21][22][23] The individual heterogeneity of normal TK ranging from 20°to 60°makes it difficult to identify hypokyphosis or hyperkyphosis. 24 Second, thoracic compensatory capacity may not manifest in kyphotic angle, only in degenerative spine.…”
Section: Discussionmentioning
confidence: 99%